Reproductive investment by females in semi-domesticated reindeer - Kojola, Ilpo; Eloranta, Eija (Rangifer, 1990)
This paper discusses maternal investment in a herd of semi-domesticated reindeer in Kaamanen, Finnish Lapland (69°N 27°E). Male-producing cows weighed 2% more at the previous conception then the female-producing cows did. The body weight of cow accounted for more of the variation of birth sex ratio than the age or the parity. The lightest cows (<C61 kg) produced a significant excess (62%) of female calves. Both the medium-sized and the largest cows gave birth to a slight, nonsignificant excess of males. In terms of weight change from one conception to the next, rearing a male to weaning was more expensive to cows than rearing a female. The frequency of reproductive failures did not, however, depend significantly upon the sex of the previous calf. The survival and growth of male and female calves related in an approximately similar fashion to maternal weight.